2013 Ambulatory Blood Pressure Monitoring Recommendations for the Diagnosis of Adult Hypertension, Assessment of Cardiovascular and other Hypertension-associated Risk, and Attainment of Therapeutic Goals: Joint Recommendations from the International Society for Chronobiology (ISC), American Association of Medical Chronobiology and Chronotherapeutics (AAMCC), Spanish Society of Applied Chronobiology, Chronotherapy, and Vascular Risk (SECAC), Spanish Society of Atherosclerosis (SEA), and Romanian Society of Internal Medicine (RSIM). (2013) - Hermida, Ramón C.; Smolensky, Michael H.; Ayala, Diana E.; Portaluppi, Francesco; Crespo, Juan J.; Fabbian, Fabio; Haus, Erhard; Manfredini, Roberto; Mojón, Artemio; Moyá, Ana; Piñeiro, Luis; Ríos, María T.; et al.
Abstract : Correlation between systolic (SBP) and diastolic (DBP) blood pressure (BP) level and target organ damage, cardiovascular disease (CVD) risk, and long-term prognosis is much greater for ambulatory BP monitoring (ABPM) than daytime office measurements. The 2013 ABPM guidelines specified herein are based on ABPM patient outcomes studies and constitute a substantial revision of current knowledge. The asleep SBP mean and sleep-time relative SBP decline are the most significant predictors of CVD events, both individually as well as jointly when combined with other ABPM-derived prognostic markers. Thus, they should be preferably used to diagnose hypertension and assess CVD and other associated risks. Progressive decrease by therapeutic intervention of the asleep BP mean is the most significant predictor of CVD event-free interval. The 24-h BP mean is not recommended to diagnose hypertension because it disregards the more valuable clinical information pertaining to the features of the 24-h BP pattern. Persons with the same 24-h BP mean may display radically different 24-h BP patterns, ranging from extreme-dipper to riser types, representative of markedly different risk states. Classification of individuals by comparing office with either the 24-h or awake BP mean as "masked normotensives" (elevated clinic BP but normal ABPM), which should replace the terms of "isolated office" or "white-coat hypertension", and "masked hypertensives" (normal clinic BP but elevated ABPM) is misleading and should be avoided because it disregards the clinical significance of the asleep BP mean. Outcome-based ABPM reference thresholds for men, which in the absence of compelling clinical conditions are 135/85 mmHg for the awake and 120/70 mmHg for the asleep SBP/DBP means, are lower by 10/5 mmHg for SBP/DBP in uncomplicated, low-CVD risk, women and lower by 15/10 mmHg for SBP/DBP in male and female high-risk patients, e.g., with diabetes, chronic kidney disease (CKD), and/or past CVD events. In the adult population, the combined prevalence of masked normotension and masked hypertension is >35%. Moreover, >20% of "normotensive" adults have a non-dipper BP profile and, thus, are at relatively high CVD risk. Clinic BP measurements, even if supplemented with home self-measurements, are unable to quantify 24-h BP patterning and asleep BP level, resulting in potential misclassification of up to 50% of all evaluated adults. ABPM should be viewed as the new gold standard to diagnose true hypertension, accurately assess consequent tissue/organ, maternal/fetal, and CVD risk, and individualize hypertension chronotherapy. ABPM should be a priority for persons likely to have a blunted nighttime BP decline and elevated CVD risk, i.e., those who are elderly and obese, those with secondary or resistant hypertension, and those diagnosed with diabetes, CKD, metabolic syndrome, and sleep disorders. (Author Correspondence:rhermida@uvigo.es orprf@unife.it ).